2017
DOI: 10.1109/tvt.2017.2695562
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility OFDM Downlink Transmission With Large-Scale Antenna Array

Abstract: Abstract-In this correspondence, we propose a new receiver design for high-mobility orthogonal frequency division multiplexing (OFDM) downlink transmissions with a large-scale antenna array. The downlink signal experiences the challenging fast time-varying propagation channel. The time-varying nature originates from the multiple carrier frequency offsets (CFOs) due to the transceiver oscillator frequency offset (OFO) and multiple Doppler shifts. Let the received signal first go through a carefully designed bea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 12 publications
(28 reference statements)
0
38
0
Order By: Relevance
“…The cone-shaped beam pattern of ULA (as shown in Fig. 3 of [17]) can guarantee that all the signals incorporated by the beam towards θ are mainly affected by the same CFO f d cos θ + ξ. Besides, the adoption of ULA only requires to design the beamforming network along the dimension of AoA for receiving all signals dispersed in the whole space.…”
Section: A Beamforming Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…The cone-shaped beam pattern of ULA (as shown in Fig. 3 of [17]) can guarantee that all the signals incorporated by the beam towards θ are mainly affected by the same CFO f d cos θ + ξ. Besides, the adoption of ULA only requires to design the beamforming network along the dimension of AoA for receiving all signals dispersed in the whole space.…”
Section: A Beamforming Networkmentioning
confidence: 99%
“…However, the approach in [17] must exploit a pilot sequence composed of two identical halves in the time domain, which limits its applicability to systems with other pilot sequences, and may not be optimal for channel estimation and subsequent data detection due to sparsity in the frequency domain [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the large-scale antenna array or massive multi-input multi-output (MIMO) has attracted increasing interests in dealing with richly scattered high-mobility scenarios due to its high spatial resolution [4]- [6]. For high-mobility downlink, the work in [7] separated the Doppler shifts by beamforming network with a large-scale antenna array and proposed a joint oscillator frequency offset and Doppler shift estimation scheme. For uplink transmissions, it has been demonstrated that the harmful effect of Doppler shift can be also mitigated by massive MIMO technique [8], [9].…”
Section: Introductionmentioning
confidence: 99%